PEMANFAATAN MEDIA ANIMASI FLASH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V MATA PELAJARAN IPA DI SDN LEBO SIDOARJO - Ima Mala Hayati (Universitas PGRI Yogyakarta, 2018)
The learning of saints in the fifth grade in SDN Lebo Sidoarjo has not been optimal. When the resaercher did the first observation, the teacher tough saints by using visual mediatwo dimention without movement, so that the student felt difficult in creating opinion adn theycould not achieve the standart that had been decided. So, It is given the solution by using theanimation flash media to solve the low result of the learning in studying saints. The reseacrh methode is Classromaction research that consists two cycles. Thesubject of thie research is the student of SDN LEBO SDA that are 41 students. The data iscollected from observation, test and field note. The data of teacher and students observationin the class are annalized in the presentage score and the score of lerning objective. The datais annalized by taking the total the score and based on the presentage clasical learningcompletting. The fieldnote that is contained the problem in the field and the solution afterannalizing the problem. The result of research shows that in the first cycle has 75% and the score is 58. Thefirst cycle in the second meetting is 81%and the score is 70. The second cycle in thefirstmeeting has 95% and the score is 100. In The secind meeting has 100% and the score is98. The presentage of the students’ activities in the first cycle and the first meeting has 83%and the score is 55. Then in he second meeting has 92% and the score is 71. The second cycleand the first meeting has 100% and the score is 92 and in the secind meting has 100% andthe score is 97. The learning result of the students can improve 58% that is from 39% in thefirst cycle becomes 97% in the second cycle.Keywords: animation flash media, IPA, a simple machine